Cephalometric evaluation of vermillion height and lip area following 1st premolar extraction in various sagittal malocclusions in adult Solan population - Dadhwal, Sahira; Aggarwal, Isha; Mittal, Sanjay; Goyal, Merry; Avasthi, Avijit (Journal of dental specialties, 2023)
Vertical thickness of the upper lip is an aesthetic determinant in a smiling face for both orthodontists. : To evaluate the vermillion height and lip area in adult patients with various sagittal malocclusion groups following 1 premolar extraction. Pre and post treatment lateral cephalograms of 50 adult patients aged between 17 to 21 years were taken. The sample was divided into 2 groups: Group I (Angles Class I Bidental protrusion) & Group II (Angles Class II div 1) with 25 subjects in each group. 2 angular and 10 linear measurments were recorded for both the groups. There were no significant differences in the vermilion height and upper lip area changes in group I, except for lower lip area. In group II significant difference were found in upper and lower lip area. When Group I and Group II were compared, only significant difference was found in lower lip area whereas vermillion height and upper lip area were found to be clinically non-significant. Extraction of four premolars can be extremely successful in improving features of the smile for the patients who have undergone treatment for Class II division 1 malocclusion and Class I Bidental protrusion. This provides a stronger evidence-based rationale for this treatment modality.